2021
DOI: 10.1007/s10570-021-03788-9
|View full text |Cite
|
Sign up to set email alerts
|

Photo-curable, double-crosslinked, in situ-forming hydrogels based on oxidized hydroxypropyl cellulose

Abstract: Chemoselective oxidation of oligo(hydroxypropyl)-substituted polysaccharides affords ketones at side chain termini, which readily condense to in situ-forming hydrogels with amine-containing polymers. This type of imine-crosslinked hydrogel displays several interesting and practically valuable properties including injectability, self-healing, tunable moduli, and ability to respond to multiple types of stimulus, so that these are promising materials for biomedical applications. As oligo(hydroxypropyl)substituted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The products of this process are very hetero geneous in terms of the degree of deacetylation, molecular weight, and other chemical parameters determining the dif ferences in their physical properties (viscosity, solubility), which, in turn, determine the possibilities of using chitosan and its biological effects (Orzali et al, 2017). In medicine, it is successfully used for tissue regeneration due to its ability to form elastic biofilms on the wound surface; it has also found application in the creation of anticoagulant and antisclerotic drugs (Skryabin et al, 2002;Chen et al, 2021). Among other applications there are cosmetics, food processing, wastewater treatment, environmental protection (Morin-Crini et al, 2019).…”
Section: Chitosanmentioning
confidence: 99%
“…The products of this process are very hetero geneous in terms of the degree of deacetylation, molecular weight, and other chemical parameters determining the dif ferences in their physical properties (viscosity, solubility), which, in turn, determine the possibilities of using chitosan and its biological effects (Orzali et al, 2017). In medicine, it is successfully used for tissue regeneration due to its ability to form elastic biofilms on the wound surface; it has also found application in the creation of anticoagulant and antisclerotic drugs (Skryabin et al, 2002;Chen et al, 2021). Among other applications there are cosmetics, food processing, wastewater treatment, environmental protection (Morin-Crini et al, 2019).…”
Section: Chitosanmentioning
confidence: 99%
“…In recent years, several in-depth studies have been reported on the role of polysaccharidespecific oxidizing agents in general and of cellulose [32,33] in particular, due to the proliferation of natural polymer-based hydrogels, in which cellulose oxidation products play the key role. The stable TEMPO radical and its derivatives, N-hydroxyphtahlimide (NHPI) and the nonpersistent phthalimide-N-oxy radical (PINO) [34,35], as well as NaIO 4, have been extensively used for the selective oxidation of polysaccharides.…”
Section: Mechanism Of Reactionmentioning
confidence: 99%
“…Both of these polysaccharides are good substrates for designing functional polysaccharide conjugates, and they each have solubility not only in water, but in certain organic solvents, permitting easier chemical modification. We hypothesized that both dextran and HPC could be readily methacrylated in organic solution [31], and that those methacrylates would be excellent acceptors for the conjugate addition of thiols, via click-like thiol-Michael addition. We further hypothesized that these efficient thiol-Michael additions would be effective methods for imparting useful new functionality to polysaccharides.…”
Section: Introductionmentioning
confidence: 99%